The Employee Engagement, Managerial Support, and Performance Recognition as Drivers of Innovation: Exploring Relationships in a Global Business Environment - Agung Surya Dwianto; Mohamad Sajili; Hetty Karunia Tunjungsari (Takaza Innovatix Labs Ltd., 2023)
This article explores the intricate dynamics of employee engagement, managerial support, and performance recognition as drivers of innovation in the context of a global business environment. Utilizing multiple linear regression analysis on data gathered from Telkomsel in Jakarta, the study reveals that while employee engagement showed a positive relationship with innovation, it did not reach statistical significance. In contrast, managerial support and performance recognition exhibited significant positive impacts on the Drivers of Innovation. The overall model was highly significant (Sig. F = 0.000), with a substantial R Square value of 0.689, indicating that nearly 69% of the variance in innovation could be explained by these factors collectively. These findings offer actionable insights for businesses seeking to enhance their innovative capacities, emphasizing the critical role of leadership support and employee recognition in fostering an adaptive and creative organizational culture within the complex landscape of the global business arena.